Functional characteristics of specialized circuit training for karate competitors - Alexandrova, A.; Penov, R.; Petrov, L.; Zaykova, D. (Journal of Applied Sports Sciences, 2018)
Successful performance in the Kumite discipline of Karate-do requires well developed aerobic and anaerobic cell-systems for supplying energy. Therefore, more and more often over the recent years, the preparation of martial arts athletes has included intensive interval training sessions following the Ta-bata method. The objective of this survey was to create a highly-intensive Tabata-based circuit training that is suitable for the functional preparation of Karate competitors and for defining the physiological and the biochemical characteristics of the training load through measuring the heart rate and the con-centration of lactate in the peripheral blood. A group of six Karate practitioners, all Kumite competi-tors, took part in the survey. They performed tree times 10 exercises with Karate-technique elements following the classical Tabata scheme of 20 seconds work with a maximum number of repetitions and 10 seconds of break. The results proved that; 1) The heart rate increased after each circuit and exceeded 180 bpm, and in the break time it went down to 120-140 bpm; 2) The lactate concentration in the blood rose progressively after the first two circuits, and after finishing the last circle an overall decrease was registered regarding this indicator (9.3 ± 3.32 vs 13.4 ± 2.39 vs 11.8 ±1.63 mmol/L, respectively). In con-clusion, the intensity of the latter circuit training model is very high because the levels of blood lactate after performing each circuit of the training were higher than the respective concentrations after Kumite competition matches at the same heart rates.